Site-specific conjugation allows modulation of click reaction stoichiometry for pretargeted SPECT imaging. Issue 8 (17th November 2018) - Mandikian, Danielle; Rafidi, Hanine; Adhikari, Pragya; Venkatraman, Priya; Nazarova, Lidia; Fung, Gabriel; Figueroa, Isabel; Ferl, Gregory Z.; Ulufatu, Sheila; Ho, Jason; McCaughey, Cynthia; Lau, Jeffrey; et al.
ABSTRACT: Antibody pretargeting is a promising strategy for improving molecular imaging, wherein the separation in time of antibody targeting and radiolabeling can lead to rapid attainment of high contrast, potentially increased sensitivity, and reduced patient radiation exposure. The inverse electron demand Diels-Alder 'click' reaction between trans -cyclooctene (TCO) conjugated antibodies and radiolabeled tetrazines presents an ideal platform for pretargeted imaging due to rapid reaction kinetics, bioorthogonality, and potential for optimization of both slow and fast clearing components. Herein, we evaluated a series of anti-human epidermal growth factor receptor 2 (HER2) pretargeting antibodies containing distinct molar ratios of site-specifically incorporated TCO. The effect of stoichiometry on tissue distribution was assessed for pretargeting TCO-modified antibodies (monitored by 125 I) and subsequent accumulation of an 111 In-labeled tetrazine in a therapeutically relevant HER2+tumor-bearing mouse model. Single photon emission computed tomography (SPECT) imaging was also employed to assess tumor imaging at various TCO-to-monoclonal antibody (mAb) ratios. Increasing TCO-to-mAb molar ratios correlated with increased in vivo click reaction efficiency evident by increased tumor distribution and systemic exposure of 111 In-labeled tetrazines. The pharmacokinetics of TCO-modified antibodies did not vary with stoichiometry. Pretargeted SPECT imaging of HER2-expressing tumors using 111 In-labeled tetrazine demonstrated robust click reaction with circulating antibody at ~2 hours and good tumor delineation for both the 2 and 6 TCO-to-mAb ratio variants at 24 hours, consistent with a limited cell-surface pool of pretargeted antibody and benefit from further distribution and internalization. To our knowledge, this represents the first reported systematic analysis of how pretargeted imaging is affected solely by variation in click reaction stoichiometry through site-specific conjugation chemistry.